2018
DOI: 10.1021/acsami.8b11714
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin- and Heparin-Loaded Poly(l-lactide-co-caprolactone) Nanofiber Aneurysm Stent Promotes Endothelialization via Vascular Endothelial Growth Factor Type A Modulation

Abstract: This study explored a new rosuvastatin calcium- and heparin-loaded poly­(l-lactide-co-caprolactone) (PLCL) scaffold for covered stents for treating aneurysms. The mechanism of rosuvastatin-induced endothelialization via vascular endothelial growth factor (VEGF)-A elevation was further explored. Rosu50, Rosu75, Rosu100, and phosphate-buffered saline (PBS) nanofibrous scaffolds were fabricated by coaxial electrospinning and observed by electron microscopy. Anticoagulation and pro-endothelialization properties we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
0
19
0
2
Order By: Relevance
“…Although the heparin coating reduced the thrombosis rate in animal experiments (22,23), it could not effectively improve late vascular patency and neointimal hyperplasia (24), suggesting that promoting the proliferation ability of ECs is crucial. In our previous study, we found that rosuvastatin-and heparin-coated stents could effectively promote early endothelialization and provide a basis for reducing long-term complications (25). Early endothelialization is the key to preventing in-stent stenosis and late thrombosis (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Although the heparin coating reduced the thrombosis rate in animal experiments (22,23), it could not effectively improve late vascular patency and neointimal hyperplasia (24), suggesting that promoting the proliferation ability of ECs is crucial. In our previous study, we found that rosuvastatin-and heparin-coated stents could effectively promote early endothelialization and provide a basis for reducing long-term complications (25). Early endothelialization is the key to preventing in-stent stenosis and late thrombosis (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Adapted with permission. [261] Copyright 2018, American Chemical Society. B) Schematic image of cells cultured on a fibrous membrane covered with fibronectin.…”
Section: Inhibiting Thrombosismentioning
confidence: 99%
“…To treat aneurysms, Liu et al used co-axial electrospinning to produce a series of novel rosuvastatin calcium-and heparin-loaded PLCL scaffolds. [261] The volume ratio of heparin to rosuvastatin calcium solution for three types of scaffolds was 450:50, 425:75, and 400:100 mL, respectively. Through SEM analysis of the RBCs on different scaffold mats and histograms analyses of the clotting time, kinetics, and clot strength, it was determined that the PLCL nanofibers incorporated with rosuvastatin and heparin at the volume ratio of 400:100 mL exhibited significant anti-coagulation properties.…”
Section: Inhibiting Thrombosismentioning
confidence: 99%
“…Похожие результаты имплантации при разработке стентов для лечения аневризм были показаны Liu и соавт., которые для создания антитромботического покрытия использовали гепарин с гиполипидемическим препаратом розувастатином кальция [41]. Розувастатин относится к классу статинов и, кроме снижения уровня холестерина в крови, имеет свойство ингибировать пролиферацию гладкомышечных клеток кровеносных сосудов и активацию тромбоцитов, стимулировать эндотелизацию и подавлять реакцию воспаления.…”
unclassified
“…Однако нановолокна получали коаксиальным электроспиннингом, в результате чего они имели в своей структуре полимерную оболочку и ядро, содержащее лекарственные препараты. Такой способ введения биоактивных веществ позволяет обеспечить их более пролонгированный выход из полимерных волокон по сравнению с эмульсионным электроспиннингом [41].…”
unclassified